The Severity of behavioral changes observed during experimental exposures of killer (Orcinus orca), long-finned Pilot (Globicephala melas), and sperm (Physeter macrocephalus) whales to naval sonar: - Miller, P.J.O.; Kvadsheim, P.H.; Lam, F.A.; Wensveen, P.J.; Antunes, R.; Alves, A.C.; Visser, F.; Kleivane, L.; Tyack, P.L.; Sivle, L.D. (2012)
This study describes behavioral changes of wild cetaceans observed during controlled exposures of naval sonar. In 2006 through 2009, 14 experiments were conducted with killer (n = 4), long-finned pilot (n = 6), and sperm (n = 4) whales. A total of 14 6-7 kHz upsweep, 13 1-2 kHz upsweep, and five 1-2 kHz downsweep sonar exposures, as well as seven Silent vessel control exposure sessions and eight playbacks of killer whale sounds were conducted. Sonar signals were transmitted by a towable source that approached each tagged subject from a starting distance of 6 to 8 km with a ramp up of source levels (from 152 to 158 to a maximum of 198 to 214 dB re: 1 μPa m). This procedure resulted in a gradual escalation of the sonar received level at the whale, measured by towed hydrophones and by tags that record movement and sound (Dtags). Observers tracked the position of each tagged animal and recorded group-level surface behavior. Two expert panels independently scored the severity of diverse behavioral changes observed during each sonar and control exposure, using the 0 to 9 point severity scale of Southall et al. (2007), and then reached consensus with a third-party moderator. The most severe responses scored (i.e., most likely to affect vital rates) included a temporary separation of a calf from its group, cessation of feeding or resting, and avoidance movements that continued after the sonar stopped transmitting. Higher severity scores were more common during sonar exposure than during Silent control sessions. Scored responses started at lower sound pressure levels (SPLs) for killer whales and were more severe during sonar exposures to killer and sperm whales than to long-finned pilot whales. Exposure sessions with the higher source level of 1 to 2 kHz sonar had more changes and a trend for higher maximum severity than 6 to 7 kHz sessions, but the order of the sessions had no effect. This approach is helpful to standardize the description of behavioral changes that occurred during our experiments and to identify and describe the severity of potential responses of free-ranging cetaceans to sonar.